(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the poetic form of mukhammas in the works of Sirojiddin Sayyid, a notable contemporary Uzbek poet. By examining the structure, thematic content, and stylistic features of selected mukhammas poems, the study reveals how Sayyid employs classical forms to express modern sensibilities, national identity, and philosophical reflection. The research highlights the fusion of tradition and innovation in his literary art.